EFFECTIVENESS OF COGNITIVE BEHAVIOURAL THERAPY AND INTEGRATIVE BEHAVIOURAL COUPLE THERAPY IN REDUCING MARITAL DISTRESS AMONG CHRISTIAN COUPLES IN CAPE COAST METROPOLIS, GHANA - FIA, Stephen Doh; OMOTOSHO, Joshua Adebisi; SEDOFIA, John (Ilorin Journal of Education, 2023)
The study investigated the efficacies of Cognitive Behavioural Therapy (CBT) and Integrative Behavioural Couple Therapy (IBCT) in reducing marital distress among Christian couples in the Cape Coast Metropolis of Ghana. The study was a quasi-experiment using the pre-test, post test, control group design. The researcher selected 60 participants who were severely distressed out of 215 married couples using a compendium of instruments on Conceptualising and Measuring “Healthy Marriages” for Empirical Research and Evaluation Studies (Task One Part II), developed by Carrano, Cleveland, Bronte-Tinkew and Moore (2003). Using systermatic sampling procedure, the 60 participants were placed in three groups of 20 participants each, for the two treatment groups (CBT and IBCT) and the control group. The data were analysed using means, standard deviations and two-way mixed ANOVA. The results revealed that CBT and IBCT therapies were effective in reducing marital distress of the participants. However, IBCT was found to be more effective than CBT. The study recommended that marriage counsellors should resort to the use of the two therapies in assisting married couples out of marital distress.